2010
DOI: 10.1158/1940-6207.capr-10-0033
|View full text |Cite
|
Sign up to set email alerts
|

Novel Application of Proton Pump Inhibitor for the Prevention of Colitis-Induced Colorectal Carcinogenesis beyond Acid Suppression

Abstract: Colitis-associated cancers arise in the setting of chronic inflammation wherein an "inflammationdysplasia-carcinoma" sequence prevails. Based on our previous findings in which the proton pump inhibitor could impose significant levels of anti-inflammatory, antiangiogenic, and selective apoptosis induction beyond gastric acid suppression, we investigated whether omeprazole could prevent the development of colitis-associated cancer in a mouse model induced by repeated bouts of colitis. Omeprazole, 10 mg/kg, was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 43 publications
3
44
1
1
Order By: Relevance
“…Omeprazole treatment decreased the levels of the anti-apoptotic proteins Bcl-2 and Bcl-X L in a dose-dependent manner. In addition to Bcl-2 and Bcl-X L , we tested caspase-3 cleavage but did not find any changes in caspase-3 in contrast to earlier findings reported by Scaringi in Jurkat cells (32) and also by Kim et al (11) in animal models. In general, Bcl-2 and Bcl-X L appear to control cell survival by inhibiting the intrinsic apoptotic pathway, which is regulated by a mitochondrial pathway, cytochrome C release, and mediated by caspase-9, caspase-3 cleavage (30).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Omeprazole treatment decreased the levels of the anti-apoptotic proteins Bcl-2 and Bcl-X L in a dose-dependent manner. In addition to Bcl-2 and Bcl-X L , we tested caspase-3 cleavage but did not find any changes in caspase-3 in contrast to earlier findings reported by Scaringi in Jurkat cells (32) and also by Kim et al (11) in animal models. In general, Bcl-2 and Bcl-X L appear to control cell survival by inhibiting the intrinsic apoptotic pathway, which is regulated by a mitochondrial pathway, cytochrome C release, and mediated by caspase-9, caspase-3 cleavage (30).…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies have demonstrated anti-inflammatory and cytoprotective actions in gastric mucosal and endothelial cells (6,8,9). Furthermore, in vivo studies support the anticancer properties of omeprazole (11,12). With regard to colon carcinogenesis, Penman et al (10) reported chemopreventive properties of omeprazole treatment reduced colon carcinogenesis in Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Omeprazol is believed to reverse the progression of inflammation-initiated or promoted carcinogenesis through antioxidative, antiinflammatory, and antimutagenic effect independent of action on gastric acid [56].…”
Section: Proton Pump Inhibitorsmentioning
confidence: 99%
“…Isolated tissues for histologic examination were spread onto a plastic sheet, fixed in 3.7% formalin for 5 hours, and prepared for paraffin tissue slides (25). The paraffin sections were stained with hematoxylin and eosin (H&E) or saved for immunohistochemical staining.…”
Section: Histopathologic Evaluationmentioning
confidence: 99%